High Throughput Study for Molecular Mechanism of Metformin Pre-Diabetic Protection via Microarray Approach - Alrawashdeh, Asma Y.; AL Shhab, Mohammad A.; Zihlif, Malek A. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2022)
Background: Metformin is a biguanide that exhibits antidiabetic, anticarcinogenic, and anti-inflammatory properties. Despite well-known pancreatic protective effects, metformin's influence on pancreatic islet β-cell is yet considerably unknown. Protecting the functional insulin-producing β-cells in the pancreas is a key therapeutic challenge in patients with type 1 (T1DM) or type 2 diabetes mellitus (T2DM). Objective: The current study aimed to analyze the protective effects of metformin on streptozocin- induced diabetic rats in T1DM in hepatic tissues. Methods: In the present study, male Wistar rats (n=24) were randomly assigned into 2 groups (n=12 for each control and test), and metformin (100 mg/kg/day) was given for 7 weeks. Afterward, diabetes was induced by streptozocin (STZ) at a single dose of 150 mg/kg. Blood glucose was examined daily before and after STZ induction. The animals were euthanized by cervical dislocation 5 days after streptozocin injection, after which liver and pancreas were harvested from each rat. Results: The biochemical analyses revealed that metformin resulted in significantly reduced plasma glucose levels and higher pancreatic insulin levels in the test group. Using a restrictive cut-off of at least 2-FC and an adjusted p-value (q-value) of ≤0.05, a sum of 747 genes for the metformin group were shown to be differentially regulated compared to controls (320 Down and 427 Up), by which they were obtained from the liver. Furthermore, the evidence is attained that metformin may hinder the loss of critical β-cells by reducing inflammatory and apoptosis signaling, promoting fatty acid β-oxidation, and inducing metabolism. Conclusion: Collectively, this study has demonstrated a decrease in blood glucose levels and a rise in insulin-levels and thus consequent prophylactic effects in metformin-given STZ-induced diabetic rats.
Keywords: prophylactic effect